Pygmies, Bushmen, and savage numbers – a case study in a sequence of bad citations - Tuominen Antti J.V. (Academic Press Inc., 2025)
There is a prevalent claim in the literature examining the history of numbers and the development of number words that some African group (“Bushmen” or “Pygmies”) counts in a particular way, where their numerals are of the form 1, 2, 3, 2+2, 2+2+1, etc. Numerous forms of this claim are traced back to their original sources through an extensive search of the available literature. The author argues that the different forms can be traced back to two early sources, which have been misquoted and bastardized along the way.
Numeraalien historiaa ja kehitystä käsittelevässä kirjallisuudessa esiintyy usein väite, että jokin afrikkalainen kansa ("bushmanit" tai "pygmit") laskee siten, että heidän numeraalinsa ovat muotoa 1, 2, 3, 2+2, 2+2+1, jne. Monia väitteen eri muotoiluja jäljitetään alkuperäislähteisiin tutkimalla laajasti saatavilla olevaa kirjallisuutta. Kirjoittaja argumentoi, että väitteen eri muodot voidaan jäljittää kahteen varhaiseen alkuperäislähteeseen, joiden sanoma on matkalla vääristynyt.